THE POLITICS OF PUBLIC HEALTH DATA: A STUDY ON DATA GOVERNANCE, PRIVACY, AND SECURITY DURING HEALTH CRISES - Sarah Zielda Najib; Nurul Hidayati; Teguh Setiawan Wibowo; Rania Khatib (Cognitionis Civitatis et Politicae, 2026)
Public health crises such as pandemics intensify the political significance of health data, exposing tensions between the need for rapid data sharing, the protection of individual privacy, and the assurance of data security. Governments increasingly rely on large-scale data collection and digital surveillance to inform policy responses, yet these practices often raise ethical, legal, and political concerns. This study aims to analyze how data governance frameworks shape the management of public health data during health crises, with particular attention to the balance between public interest, privacy rights, and data security. The research employs a qualitative research design based on document analysis and comparative policy review, examining national regulations, emergency health policies, and international guidelines related to health data governance. The findings indicate that data governance during health crises is strongly influenced by political priorities, institutional capacity, and levels of public trust. Weak regulatory clarity and limited oversight mechanisms tend to exacerbate privacy risks and public resistance, while transparent governance models and robust security protocols enhance data legitimacy and compliance. The study concludes that effective public health data governance requires an integrated approach that aligns legal safeguards, ethical principles, and technological security with crisis-driven decision-making. Strengthening accountability and transparency is essential to ensuring that public health objectives do not undermine fundamental rights during emergencies.